THE RELATIONSHIP OF KNOWLEDGE ABOUT COVID-19 WITH COMMUNITY PERCEPTIONS OF THE COVID-19 VACCINATION PROGRAM - Murtiyani, Ninik; Yulianto, Yulianto; Adhimah, Lailatul (Universitas Airlangga, 2021)
Introduction: There are so many issues that affect information about the Covid-19 vaccine, such as safety and vaccines that have not been proven to be effective in preventing someone from being infected with Covid-19 again. Knowledge will also affect the public's perception of the Covid-19 vaccination program. Methods: The design of this study was a cross-sectional approach. with a population of 127 respondents and a sample of 96 people. The sampling method uses simple random sampling, data collection uses a questionnaire. The variables in this study are the dependent variable on perceptions of the Covid-19 vaccination program in the community and the independent variable on knowledge about Covid-19. Spearman Rho test with < 0.05. Result: respondents' knowledge (88.5%) is good. Respondents' perception of the COVID-19 vaccination program (90.6%) was positive. The results of the Spearman rho test showed = 0.018 < = 0.05. Conclusion: there is a relationship between knowledge about Covid-19 and the perception of the Covid-19 vaccination program in the community in Sumari Hamlet, Sumari Village, Sitsampeyan District, Gresik